Impact of measles vaccination strategies on vaccination rates in low-income and middle-income countries: a systematic review and meta-analysis - Andrew Hayen; Kiddus Yitbarek; Mirkuzie Woldie; Firew Tekle Bobo; Jane Frawley; Abela Mahimbo; Meru Sheel (BMJ Global Health)
Introduction While many interventions aim to raise measles vaccination coverage in low-income and middle-income countries (LMICs), their overall effectiveness and cost-effectiveness are unknown. We did a review to identify and synthesise scientific research that evaluated the impact and cost-effectiveness of measles vaccination strategies on measles vaccination coverage, timeliness, hospitalisation rates, and mortality.Methods In this review, we searched for English-language articles published between 2012 and July 2023 in eight databases, including PubMed, ProQuest, MEDLINE (Ovid), Embase (Ovid), CINAHL, Scopus, Web of Science and the Cochrane Database of Systematic Reviews. We also included relevant grey literature sources. The review focused on studies evaluating the impact of vaccination strategies on vaccination-related outcomes in children under 5. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines throughout the process, we used Covidence software to manage most review activities. Two independent reviewers screened articles, assessed their quality using the Joanna Briggs Institute guidelines and extracted data using a predefined electronic tool. We predetermined measles vaccination coverage and timeliness as the primary outcomes, with hospitalisation and mortality as secondary outcomes. A random-effects model was employed for the meta-analysis.Results We identified 44 articles, of which 14 were included in the meta-analysis. The meta-analysis indicated that vaccination-targeting interventions such as vaccination reminders, cash incentives, community engagement and health education activities increase measles vaccination coverage (RR 1.19, 95% CI 1.10 to 1.27). Our analysis also indicated that interventions such as vaccine reminders, educational programmes and incentives improved timely vaccination. Furthermore, we identified cost-effective strategies such as geographically informed microplanning, unrestricted vial opening, supplementary immunisation activities, community engagement, outreach programmes and financial incentives.Conclusion Most of the identified vaccination interventions significantly improve measles vaccination coverage and timeliness in LMICs while remaining cost-effective. Tailoring these interventions to local contexts is crucial for maximising their effectiveness in protecting children from measles and its adverse consequences.PROSPERO registration number CRD42023433125.